Evidence-Based Practice in Forensic Mental Health Nursing: A Critical Review. Issue 4 (October 2018) - Byrt, Richard; Spencer-Stiles, Theresa A.; Ismail, Ismail
Abstract : Method: Literature searches of databases, particularly CINAHL, using key phrases were undertaken. Results: Some authors argue that there is a lack of evidence in forensic mental health (FMH) nursing, with few randomized controlled trials and other methods providing definitive, generalizable evidence. However, literature searches revealed randomized controlled trials of relevance to FMH nursing, many qualitative studies by FMH nurses, and arguments for clinical experience and knowledge of service users, and the latter's views, as sources of evidence. Discussion and Implications for Nursing Practice: Research findings can be applied to practice, both directly and indirectly. Examples are given of ways that evidence can be used to inform FMH nursing interventions related to therapeutic ward environments, including communication, therapeutic relationships, preventing retraumatization, and enabling physical health. The complex nature of "evidence" is considered in relation to risk assessment and management. Conclusions for Nursing Practice: FMH nursing can be based on a wide range of sources of evidence. The types of evidence used in practice depend on individual service users' needs and views. In evaluating evidence, it is necessary to be aware of its complex, diverse nature. A distinction can be made between definitive, widely generalizable research findings and evidence with limited generalizability, requiring FMH nurses' judgments about whether it is applicable to their own area of practice. Recommendations for related education and research are made. Abstract : Supplemental digital content is available in the text.